Safety and immunogenicity of the malaria vaccine candidate GMZ2 in malaria-exposed, adult individuals from Lambaréné, Gabon - Mordmüller, Benjamin Gottlieb; Szywon, Katja; Greutelaers, Benedikt; Esen, Meral; Mewono, Ludovic; Treut, Carolin; Mürbeth, Raymund E.; Chilengi, Roma; Noor, Ramadhani; Kilama, Wen L.; Imoukhuede, Egeruan B.; Imbault, Nathalie; et al. (Vaccine, 2010)
Malaria is still one of the major public health threats in sub-Saharan Africa. An effective vaccine could be a sustainable control measure that can be integrated into existing health infrastructures. The malaria vaccine candidate GMZ2 is a recombinant fusion protein of conserved parts of Plasmodium falciparum Glutamate Rich Protein and Merozoite Surface Protein 3 adjuvanted with aluminium hydroxide. GMZ2 is immunogenic and well tolerated in malaria-naive adults from Germany. To assess safety and immunogenicity in malaria-exposed individuals, 40 adults from Lambaréné, Gabon were randomly assigned to receive either 100μg GMZ2 or a rabies control vaccine three times in monthly intervals. Both vaccines were well tolerated. One month after a full course of vaccination, GMZ2-vaccinated individuals had 1.4-fold (95% confidence interval: [1.1, 1.7]) higher baseline-corrected anti-GMZ2 antibody levels and more GMZ2-specific memory B-cells compared to the rabies group (p=0.039), despite a high prevalence of GMZ2-specific immune reactivity due to previous intense exposure to P. falciparum.